EEKTIFITAS EDUKASI GIZI TERHADAP TINGKAT PENGETAHUAN GIZI SEIMBANG PADA SISWA SEKOLAH DASAR: Peran edukasi gizi dalam mencegah masalah gizi pada anak usia sekolah - Tria Eni; Rafika Devi; Yulia Retno Safitri (PPPM Stikes Banyuwangi, 2026)
Abstract: Malnutrition is associated with decreased cognitive function, impaired learning concentration, and inhibited physical growth, while overnutrition increases the risk of degenerative diseases such as obesity, diabetes mellitus, and cardiovascular disease in the future. Nutritional problems among elementary school children include a lack of knowledge about balanced nutrition and insufficient energy and protein intake below the minimum requirements. The purpose of this community service program (PKM) was to increase school involvement in providing nutritional interventions in the form of nutrition education for students in order to improve their level of knowledge. The method used was a cross-sectional survey. The stages of this PKM activity began with a survey conducted at SDN 02, followed by preparation and implementation of nutrition education using LCD media, PowerPoint materials, leaflets, and games. After the education session, an evaluation was conducted using a questionnaire. The results showed that among the sample of 50 students, the average (mean) pretest score was 56.2 with a standard deviation of 10.5, while the average posttest score increased to 82.4 with a standard deviation of 8.7. Statistical test results obtained a p-value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest scores. Therefore, balanced nutrition education was proven effective in improving students’ knowledge.